Effect of an internet-based sexually transmitted infection testing and results service on diagnoses and testing uptake: a single-blind, randomised controlled trial. (November 2017) - Wilson, Emma; Free, Caroline; Morris, Tim P; Syred, Jonathan; Menon-Johansson, Anatole S; Palmer, Melissa J; Barnard, Sharmani; Rezel, Emma; Baraitser, Paula
Abstract: Background: Sexually transmitted infection (STI) self-sampling kits accessed via the internet (e-STI testing) is recommended despite a limited evidence base. We aimed to evaluate the effect of an e-STI testing service (chlamydia, gonorrhoea, HIV, and syphilis) on diagnoses and testing uptake, when delivered alongside usual care. Methods: Individuals aged 16–30 years, resident in two London boroughs, with at least one sexual partner in the previous 12 months and willing to test, were recruited in community settings. An independent computer-based randomisation programme allocated participants to an e-STI testing service (intervention) or a website with signposting to local sexual health clinics (control). Primary outcomes at 6 weeks were diagnosis of any STI and completion of any STI test. 3000 participants were required to detect a relative risk of 3·5 for STI diagnoses, with 90% power at a 5% level of significance, allowing for 10% losses to follow up. Laboratory staff and outcome assessors were blinded to treatment allocation. All analyses were intention to treat. We used multivariate imputation by chained equations (MICE) for the primary analyses. All participants provided written informed consent. Ethics approval was granted by the National Research Ethics Service Committee London-Camberwell St Giles (ref 14/LO/1477). This trial is registered with Current Controlled Trials, number ISRCTN13354298. Findings: 2072 participants were randomised (after nine exclusions, 1031 intervention, 1032 control, mean age 23 years, SD 3·6). Response rate was 84%. 1031 participants were analysed in the intervention and 1032 in the control group. At 6 weeks, 50·0% of the intervention group completed an STI test compared with 26·6% of the control group (relative risk 1·87, 95% CI 1·63–2·15; p<0·0001). 2·8% of the intervention group versus 1·4% of the control group were diagnosed with an STI (2·10, 0·94–4·70; p=0·079). The proportions of participants treated were 1·1% for intervention and 0·7% for controls (1·72, 0·71–4·16; p=0·231). No heterogeneity was observed in pre-specified subgroup analyses. Time to test was lower in the intervention arm than in the control arm (restricted mean 28·8 days [SE 0·5] vs 36·5 [0·4], p<0·0001). No differences were observed for time to treatment. Interpretation: The findings show that e-STI testing increased testing uptake. We were underpowered for the analyses of STI diagnoses and STI cases treated but our estimates suggested effects in the expected direction. Future service innovations may ensure that gains in testing and diagnoses translate into similar gains in cases treated. e-STI services require long-term evaluation. Funding: Guy's and St Thomas' Charity.